A study on mechanical and thermal properties of polypropylene/recycled acrylonitrile butadiene rubber/palm kernel shell composites with maleic anhydride grafted polypropylene as compatibilizer. (30th October 2017) - Affandi, Ranggita D.; Ragunathan, Santiagoo; Ismail, Hanafi; Sam, SungTing
Abstract : Thermal properties of polypropylene (PP)/recycled acrylonitrile butadiene rubber (rNBR)/palm kernel shell (PKS) composites with maleic anhydride grafted polypropylene (MAH‐g‐PP) as compatibilizer were carried out. The properties of PP/rNBR/PKS with and without MAH‐g‐PP compatibilization were studied at six different loadings (i.e., 100/0/15, 80/20/15, 70/30/15, 60/40/15, 50/50/15, and 40/60/15 phr). MAH‐g‐PP loading for each composites was fixed at 4 phr. The effects of MAH‐g‐PP on thermal, mechanical, morphological properties were investigated. The results showed that the addition of MAH‐g‐PP exhibited better thermal stability compared to uncompatibilized composites. The temperature degradation ( T deg ) were slightly increased around 5%. Total weight losses of MAH‐g‐PP compatibilized composites lower were then compared to uncompatibilized composites. The melting temperature ( T m ) was slightly increased about 1–2°C with addition of MAH‐g‐PP. The crystallinity ( X c ) of the composites increased from 18 to 42% with addition of MAH‐g‐PP. Higher tensile strength, Young's modulus and impact strength but lower elongation at break were also obtained in MAH‐g‐PP compatibilized composites. This was shown by the scanning electron microscope which indicated improved adhesion of the PKS filler with PP/rNBR matrices in the presence of MAH‐g‐PP. J. VINYL ADDIT. TECHNOL., 24:E125–E132, 2018. © 2017 Society of Plastics Engineers